Malaysian form 6 students' perception towards the English language Listening online classes during the Covid-19 Pandemic. - Dakshayani, Jayakumar (2021)
The worldwide COVID-19 pandemic has recently altered many aspects of education. The primary goal of this research was to determine Malaysian Form 6 students' attitudes toward English language Listening online classes during the Covid-19 Pandemic. The perceptions of students were assessed using five criteria: student satisfaction, interaction (teacher-student and student-student), ease of use, and teachers' strategies. This survey included 273 Form 6 students. A Google Form link was used to distribute an online questionnaire to the students. The survey used a 5-point Likert scale. The findings revealed that the English language online listening classes held during the Covid-19 Pandemic were perceived neutrally by the students. It means that the students lacked the necessary experience to properly evaluate the phenomenon. Not only that, but students have stated that they are still having difficulties enrolling in listening classes. Finally, this study employed the use of mixed-method research design with open-ended questions to gain a more in-depth understanding of the phenomenon.